Do spatially homogenizing and heterogenizing processes affect transitions between alternative stable states? :Powerpoint - van de Vijver, C.A.D.M. (University of Twente, 2020)
Alternative stable states; Effect of heterogeneity on these dynamics; Impact of homogenizing processes Spatial processes; What happens with both heterogenizing and homogenizing processes at the same time?; Example ecosystem: Savannas; Positive feedback; Non-spatial model.